Home range of the mouse Phyllotis osilae in forest fragments of Polylepis subtusalbida with different habitat matrix - Rojas-Estrada, Romeo; Aguirre, Luis F.; Navarro Antezana, Freddy (THERYA, 2020)
Home range is an aspect of ecology that allows us to understand the mechanisms and spatial relationships that underlie habitat choice and animal responses to environmental change. However, studies on this subject have been focused mainly on medium and large mammals, while those on small mammals are scarce. Small mammals play important roles in maintaining ecological processes, such as the survival of several plant species. Phyllotis osilae is a phyllotine rodent, which functions as a potential seed disperser for Polylepis subtusalbida, a tree that is endemic and categorized as Vulnerable (VU) for Bolivia. The forests of P. subtusalbida are highly fragmented, with reforestation with introduced species such as Pinus radiata and Eucalyptus globulus. The question we pose for this study is: how does the home range of P. osilae vary between fragments of P. subtusalbida with different types of matrix (natural grassland and exotic tree plantations)? The study was carried out on four fragments of P. subtusalbida in Tunari National Park in the city of Cochabamba, Bolivia: two fragments in the exotic tree plantation matrix (Pajcha locality) and two in the natural grassland matrix (San Miguel locality). For telemetry purposes, radio collars were installed on 16 individuals. The home ranges were calculated using the Minimun Convex Polygon (MCP) at 95 %, in the same way the Kernel density (KDE) was estimated at 95 %. The percentage of presence of P. subtusalbida and matrix trees within each home range was determined, with an area interval between 50.5 m2 and 3,010 m2. No significant differences were found between both matrices regard to the area of activity; however, in the comparison of the percentages of presence of P. subtusalbida trees and matrix, significant differences were found. Our results for home ranges show that the matrix would not have an effect on the area, but on its mobility; this is evidenced by the absence of movements of P. osilae from the fragments to the exotic matrix. In this case, the exotic tree matrix is operating as a barrier and is reflected in the almost total absence of this vegetation matrix in the home range. P. osilae may be playing an important role in the recovery and conservation of these ecosystems, so knowing aspects of their natural history as well as their responses to fragmentation is of great importance in understanding the fate of the Polylepis forests.